Program nauczania prawa na Wydziale Prawa Uniwersytetu Mikołaja Kopernika w Toruniu w latach 1945–1962 - Budkiewicz-Szczupak, Lucyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of the article is to present the core law curriculum at the Faculty of Law, Nicolaus Copernicus University in Toruń in 1945–1962, that is at the beginning of the functioning of the Faculty. The author discusses the origins and changes in the teaching of law in the analysed period.
Keywords: program studiów prawniczych; nauczanie prawa; Wydział Prawa; Uniwersytet Mikołaja Kopernika